2020
DOI: 10.1111/iwj.13314
|View full text |Cite
|
Sign up to set email alerts
|

Biological dermal templates with native collagen scaffolds provide guiding ridges for invading cells and may promote structured dermal wound healing

Abstract: Dermal substitutes are of major importance in treating full thickness skin defects. They come in a variety of materials manufactured into various forms, such as films, hydrocolloids, hydrogels, sponges, membranes, and electrospun micro‐ and nanofibers. Bioactive dermal substitutes act in wound healing either by delivery of bioactive compounds or by being constructed from materials having endogenous activity. The healing success rate is highly determined by cellular and physiological processes at the host‐bioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…With regard to this, the native col scaffold has been proven effective for cell attachment and proliferation, particularly at the wound site. Interestingly, the cells at the wound site appeared to be symmetrical and aligned in accordance with the native Col scaffold [ 77 ]. Nonetheless, an in vitro study proved that col scaffolds successfully accelerated healing by enhancing proliferation of fibroblasts [ 78 ] by increasing biological and structural integrities which resembled the native extracellular matrix (ECM) at the wound site [ 79 ].…”
Section: Differences Between Collagen and Gelatinmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to this, the native col scaffold has been proven effective for cell attachment and proliferation, particularly at the wound site. Interestingly, the cells at the wound site appeared to be symmetrical and aligned in accordance with the native Col scaffold [ 77 ]. Nonetheless, an in vitro study proved that col scaffolds successfully accelerated healing by enhancing proliferation of fibroblasts [ 78 ] by increasing biological and structural integrities which resembled the native extracellular matrix (ECM) at the wound site [ 79 ].…”
Section: Differences Between Collagen and Gelatinmentioning
confidence: 99%
“…Being biocompatible, they are beneficial and superior compared to other available natural products. Col is naturally found in the human body while gelatin is a hydrolysed form of Col. Studies done by Dill and Morgelin (2020) [ 77 ] and Wiegand et al, (2016) [ 87 ] showed that native Col provided a 3D microenvironment that stimulated cell proliferation and aided the migration of keratinocytes and fibroblasts to the physiologic locations during wound healing. Through their in vitro investigations, they noticed that fibroblasts and keratinocytes attached to Col with high affinities.…”
Section: Collagen and Gelatin For Skin Wound Healingmentioning
confidence: 99%
“…With regard to pore size and crosslink density, it is worth mentioning that the optimal values found by the Yannas team for their DRT are currently used as a gold standard for the development of alternative dermal substitutes. However, the DRT does not present the native collagen banding (it is estimated to have only a 5% residual banding) (Yannas, 2005) while having a microporous sponge-like structure that does not really mimic the fibrillar network of the skin ECM (Dill and Mörgelin, 2020). This relatively poor mimesis of the native collagen architecture may be one of the critical features leading to suboptimal skin regeneration.…”
Section: Skin (Dermal Templates)mentioning
confidence: 99%
“…Indeed, more recent studies seem to suggest that the preservation of the native tissue structure is highly desirable for improved skin regeneration (Böhm et al, 2017;De Angelis et al, 2018;Tati et al, 2018;Dill and Mörgelin, 2020). When comparing different collagen-based dermal substitutes, all obtained by freeze-drying but varying for the collagen source and the related processing steps (e.g., collagen extraction, aqueous processing, and crosslinking), those with a dermislike fibrillar network and/or those retaining the native collagen banding have been shown to promote in vitro important biological processes involved in tissue regeneration, such as the binding and inactivation of proteases (Tati et al, 2018), an accelerated adhesion, migration and proliferation of cells in the scaffolds (Böhm et al, 2017;Dill and Mörgelin, 2020), an improved cell morphology (Dill and Mörgelin, 2020), and a higher downregulation of the myofibroblast phenotype (Dill and Mörgelin, 2020). Interestingly, in a recent clinical study, an alternative dermal template based on native type I collagen has been shown to lead to accelerated angiogenesis and tissue formation in the short term, as well as to a better clinical outcome in the long term, compared to the Integra R DRT (De Angelis et al, 2018).…”
Section: Skin (Dermal Templates)mentioning
confidence: 99%
“…Collagen Collagen has been found as the frequent protein in terrestrial and marine animals with desirable tensile strength, biocompatibility, bioavailability, and biodegradability properties for various therapeutic applications particularly tissue engineering (Lim et al 2019;Divakar et al 2019). Scaffold of collagen can attract and guide the migration of broblast cells along a connective tissue matrix (Dill and Mörgelin 2020). By interaction with blood platelets, this polymer can lead to the wound closure and prompt the acceleration of hemostatic phase of wound healing (Ding et al 2020).…”
Section: Protein Polymersmentioning
confidence: 99%